2014
DOI: 10.1128/aem.03790-13
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic Factors Affecting the Persistence of Avian Influenza Virus in Surface Waters of Waterfowl Habitats

Abstract: dAvian influenza (AI) virus can remain infectious in water for months, and virus-contaminated surface water is considered to be a source of infection within wild waterfowl populations. Previous work has characterized the effects of pH, salinity, and temperature on viral persistence in water, but most of that work was done with modified distilled water. The objective of this study was to identify the abiotic factors that influence the duration of AI virus persistence in natural surface water. Surface water samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 35 publications
3
44
0
Order By: Relevance
“…Studies have shown that a high persistence of influenza A viruses in environmental waters which can remain infectious over a long period, depending on the strain types and environmental factors (e.g. salinity, temperature, pH) (Dublineau et al, 2011;Keeler et al 2013Keeler et al , 2014Stallknecht et al, 1990;Webster et al, 1992). In this study, a high detection rate of influenza A virus was found (64.5%), which is higher than those previously reported in France (44.4%) (Deboosere et al, 2011) and Netherlands (40%) (Heijnen and Medema, 2011).…”
Section: Pathogensmentioning
confidence: 99%
“…Studies have shown that a high persistence of influenza A viruses in environmental waters which can remain infectious over a long period, depending on the strain types and environmental factors (e.g. salinity, temperature, pH) (Dublineau et al, 2011;Keeler et al 2013Keeler et al , 2014Stallknecht et al, 1990;Webster et al, 1992). In this study, a high detection rate of influenza A virus was found (64.5%), which is higher than those previously reported in France (44.4%) (Deboosere et al, 2011) and Netherlands (40%) (Heijnen and Medema, 2011).…”
Section: Pathogensmentioning
confidence: 99%
“…The virus is present in the faeces of wild waterfowl, water contaminated by their faeces, domestic poultry secretions (respiratory and faeces) and aerosolised respiratory secretions from infected animals. The virion is usually very labile (Markey et al, 2013b) but it has been shown that avian influenza virus is infectious for months in low temperature water and for over a week in water at 22°C (Hinshaw et al, 1979;Markwell and Shortridge, 1982) with increased survival when water has neutral to basic pH (7.0-8.5) and low ammonia concentrations (Keeler et al, 2014). It is also stable in frozen lakes (Shoham et al, 2012), allowing maintenance in the environment and infection of waterfowl from year to year.…”
Section: Classification and Biophysical Propertiesmentioning
confidence: 99%
“…For H5N1 and H7N2 for example, it has been reported that these viruses retained their infectivity for a few days in faeces or manure kept at ambient temperature (Lu et al, 2003;Songserm et al, 2005).Tenacity, i.e. In general, avian influenza viruses are more stable with decreasing temperatures and in fresh to brackish salinities (Brown et al, 2007;Keeler et al, 2014). aerosol, water, faeces, carcass/meat) and environmental conditions (temperature, salinity, pH, protein content, among many others) (EFSA, 2008).…”
Section: Possible Introduction By Persons Vehicles Equipment and Fomentioning
confidence: 99%